Ce-Ni mixed oxide as efficient catalyst for H-2 production and nanofibrous carbon material from ethanol in the presence of water - Fang, Wenhao; Pirez, Cyril; Capron, Mickael; Paul, Sebastien; Raja, Thirumalaiswamy; Dhepe, Paresh Laxmikant; Dumeignil, Franck; Jalowiecki-Duhamel, Louise (RSC Advances, 2012)
Hydrogen production from ethanol steam reforming (H2O/C2H5OH = 3) was studied over Ce-Ni based catalysts issued from different preparation methods (co-precipitation (CP), impregnation (IMP) and incipient wetness impregnation (IWI)). Catalysts prepared by the CP method exhibit higher activity and much better stability compared to the other two types of catalysts. The Ni1CeOY-CP catalyst is able to completely convert ethanol at 450 degrees C to H-2, CO2 and CH4 (almost no CO is observed), with a H-2 yield of 3 moles of hydrogen produced per mole of ethanol converted. A very high H-2 yield of 4.6 mol mol(EtOH)(-1) is achieved over the Ni1CeOY-CP mixed oxide at 650 degrees C. Correlations between the preparation method, catalytic activity and stability, and type of carbon deposition are discussed. The CP method forms very active small sized NiO (15 nm) and CeO2 (4 nm) nanoparticles, leading to the formation of a lower amount of carbon deposition in the form of nanofibrous carbon materials, the size of which depends on the Ni related nanoparticles. For CP catalysts, the graphitic filaments obtained correspond to carbon nanofibers (CNFs) and carbon nanotubes (CNTs) with a much smaller and homogenous size compared to the filamentous carbon formed over the catalysts issued from the other preparation methods, in relation to the active particles size. The catalytic stability is attributed to the type of carbon formed.

Highly loaded well dispersed stable Ni species in NiXMg2AlOY nanocomposites: application to hydrogen production from bioethanol - Fang, Wenhao; Paul, Sebastien; Capron, Mickael; Biradar, Ankush V.; Shubhangi B. Umbarkar; Dongare, Mohan K.; Dumeignil, Franck; Jalowiecki-Duhamel, Louise (Applied Catalysis B-Environmental, 2015)
Inexpensive NiXMg2AlOY nanocomposites with high Ni content (Ni wt% > 40%) are developed as efficient catalysts for the sustainable hydrogen production from a mixture of ethanol and water at low temperature. The NiXMg2AlOY nanocomposites are composed of small and uniform nanoparticles (4-6 nm) of NiO, Ni-Mg-(Al)-O and/or MgO. The strong interactions existing between Ni2+ cations and Mg2+ and/or Al3+ cations either in the Ni-Mg-(Al)-O solid solution and/or at the interface of nanoparticles of NiO and/or Ni-Mg-(Al)-O make the catalyst highly active and stable. The behavior of the solids is analyzed in the presence of low and high concentrations of ethanol while maintaining a H2O/EtOH molar ratio of 3. The NiXMg2AlOY catalysts are shown to be efficient toward H-2 production between 250 and 650 degrees C. In the presence of low concentration of ethanol, on the highly loaded Ni compound (Ni12Mg2AlOY), total conversion of ethanol is obtained at 250 degrees C without formation of CO and carbon, and at 300 degrees C a H-2 yield of 3 mol moletEtOH(-1) is obtained without the formation of CO, exhibiting a remarkable stability with the time on stream even if some carbon is formed. In high concentration of ethanol, total conversion of ethanol is obtained at 450 degrees C on the highly loaded Ni compound (Ni12Mg2AlOY). In such conditions, a stable co-generation of carbon nanofibrous materials which amount increases with Ni content is also obtained. The catalytic stability is related to the type and morphology of the carbon species formed. The correlations among the catalyst properties, the catalytic performances and the characterizations are thoroughly discussed. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Ethanol; Hydrogen; Nanofibrous carbon; nickel oxide; Steam reforming